A survey of current and anticipated use of standard and specialist equipment by UK optometrists. (26th August 2014) - Dabasia, Priya L.; Edgar, David F.; Garway‐Heath, David F.; Lawrenson, John G.
Abstract Purpose To investigate current and anticipated use of equipment and information technology (IT) in community optometric practice in the UK, and to elicit optometrists' views on adoption of specialist equipment and IT. Methods An anonymous online questionnaire was developed, covering use of standard and specialist diagnostic equipment, and IT. The survey was distributed to a random sample of 1300 UK College of Optometrists members. Results Four hundred and thirty‐two responses were received (response rate = 35%). Enhanced (locally commissioned) or additional/separately contracted services were provided by 73% of respondents. Services included glaucoma repeat measures (30% of respondents), glaucoma referral refinement (22%), fast‐track referral for wet age‐related macular degeneration (48%), and direct cataract referral (40%). Most respondents (88%) reported using non‐contact/pneumo tonometry for intra‐ocular pressure measurement, with 81% using Goldmann or Perkins tonometry. The most widely used item of specialist equipment was the fundus camera (74% of respondents). Optical Coherence Tomography (OCT) was used by 15% of respondents, up from 2% in 2007. Notably, 43% of those anticipating purchasing specialist equipment in the next 12 months planned to buy an OCT. 'Paperless' records were used by 39% of respondents, and almost 80% of practices used an electronic patient record/practice management system. Variations in responses between parts of the UK reflect differences in the provision of the General Ophthalmic Services contract or community enhanced services. There was general agreement that specialised equipment enhances clinical care, permits increased involvement in enhanced services, promotes the practice and can be used as a defence in clinico‐legal cases, but initial costs and ongoing maintenance can be a financial burden. Respondents generally agreed that IT facilitates administrative flow and secure exchange of health information, and promotes a state‐of‐the‐art practice image. However, use of IT may not save examination time; its dynamic nature necessitates frequent updates and technical support; the need for adequate training is an issue; and security of data is also a concern. Conclusion UK optometrists increasingly employ modern equipment and IT services to enhance patient care and for practice management. While the clinical benefits of specialist equipment and IT are appreciated, questions remain as to whether the investment is cost‐effective, and how specialist equipment and IT may be used to best advantage in community optometric practice.